Russian market power in international wheat exports: Evidence from a residual demand elasticity analysis - Kerstin Marit Uhl; Oleksandr Perekhozhuk; Thomas Glauben (Journal of Agricultural & Food Industrial Organization, 2019)
Russia has emerged as a major wheat exporter since the beginning of the 2000s, and today, it possesses high market shares in several wheat-importing countries in the Middle East and North African region. This has raised concerns that Russia might abuse its dominant market position by pricing above marginal cost. Using a novel dataset with weekly information on Russian wheat exports, we apply the residual demand elasticity method to analyze the pricing behavior of Russia in its two most important export markets, i.0.167eme. Egypt and Turkey. Our estimation results reveal that Russia behaves competitively in Egypt while it exerts market power in Turkey with an estimated mark-up of 13.50.166em%.
Keywords: 330; Russian wheat exports; market power; residual demand elasticity approach